A study on the impact of SO2 on CO2 injectivity for CO2 storage in a Canadian saline aquifer. (15th December 2016) - Wang, Zhiyu; Wang, Jinsheng; Lan, Christopher; He, Ian; Ko, Vivien; Ryan, David; Wigston, Andrew
Highlights: New observations from experiments for CO2 storage evaluations are reported. SO2 in CO2 increased salt precipitation, and addition of O2 increased it further. Quartz dissolution was much faster when SO2 and O2 were added to CO2 . A correlation appears to exist between quartz dissolution and salt precipitation. A model is developed to elucidate the above correlation and the effect of SO2 . Abstract: Potential effects of SO2 as an impurity on CO2 injectivity for CO2 storage in a targeted sandstone saline aquifer in western Canada were investigated. Batch experiments using rock and brine samples in contact with supercritical CO2 and CO2 mixtures with SO2 were conducted in high-pressure reactors for 45 days. The results suggest that SO2 increased precipitation of sodium chloride and calcium sulfate dehydrate, and also increased the dissolution of quartz. Moreover, the precipitation of sodium chloride appeared to be concurrent with the dissolution of quartz, the predominant constituent of the rock. The concurrent precipitation of sodium chloride and dissolution of quartz could be attributed to taking up of water by H4 SiO4 that reduces the number of water molecules in the hydration shells of Na+ and Cl− ions in highly concentrated brine. According to this view, the dissolution of quartz, which would be much slower than the reassociation of dissolved sodium chloride ions, is limiting the rate of sodium chloride precipitation. The rate of quartz dissolution was estimated based on the present experimental data, which could be used to assess salt precipitation and determine suitable operation conditions for CO2 injection. The findings of this work should also be applicable to acid gas injection in oil and gas industry.